The Online Learning in Covid 19 Pandemic Era: College Student Obstacle - Juwita Crestiani M (Institut Agama Islam Negeri Palopo, 2021)
The impact of Covid-19 on the world of education is very large and is felt by various parties, especially teachers, school principals, students and also parents. Teaching and learning activities through online are very new activities, given that online learning activities are learning activities by utilizing electronics and the internet in the delivery of learning materials. This research deals with the college student obstacle of the seventh semester at Palopo Cokroaminoto University during the online learning in Covid 19 Pandemic Era. The subject of this research was the college student obstacle of the seventh semester at Palopo Cokroaminoto University in academic year 2021. The total number of subject was 15 students. The researcher used the random sampling. The instrument in this research is interview and analyzed by qualitative. Based on the findings and discussion in the previous chapter, the researcher concludes that the college student obstacle of the seventh semester at Palopo Cokroaminoto University during the online learning in Covid 19 Pandemic Era are bad network, quota data, and unsupported facilities such as hp, good electric current.